Effects of Flavonoids Extracted from Citrus aurantium on Performance, Behavior, and Rumen Gene Expression in Holstein Bulls Fed with High-Concentrate Diets in Pellet Form - Montserrat Paniagua; Francisco Javier Crespo; Anna Arís; Maria Devant (Animals, 2021)
Flavonoid supplementation may modify the behavior and rumen inflammatory response of fattening bulls, and this could be related to the concentrate presentation (mash or pellet) form. In the present study, 150 Holstein bulls (183.0 ± 7.53 kg BW and 137 ± 1.8 d of age) were randomly allocated to one of eight pens and assigned to control (C) or (BF) (Citrus aurantium, Bioflavex CA, HealthTech Bio Actives, Spain, 0.4 kg per ton of concentrate of Bioflavex CA, 20% naringin). Concentrate (pellet) intake was recorded daily, and BW and animal behavior fortnightly. Animals were slaughtered after 168 d of study, and ruminal epithelium samples were collected for gene expression analyses. Treatment did not affect animal performance; however, BF supplementation reduced agonistic interactions and oral non-nutritive behaviors and increased the time devoted to eating concentrate and ruminating activity (p < 0.05). The gene expression of some genes in the rumen epithelium was greater or tended to be greater in BF than C bulls (bitter taste receptor 16, cytokine IL-25, β-defensin; p < 0.10; pancreatic polypeptide receptor 1 and tumor necrosis factor alpha; p < 0.05). In conclusion, flavonoid supplementation modifies the expression of genes in the rumen epithelium that could be related to inflammation and animal behavior modulation.